Ho Chi Minh’s Ideology on Establishing a Streamlined, Effective, and Efficient Democratic Administration and its Application to the Construction of the Political System Apparatus in Contemporary Vietnam - Phuc, Nguyen The; Thu, Hoang Thi Huong; Minh, Nguyen Thanh; Suong, Nguyen Thi Kieu (Journal of Posthumanism, 2025)
This study examines Ho Chi Minh’s ideology on establishing a streamlined, effective, and democratic public administration, highlighting its enduring relevance to contemporary Vietnam. Using historical-logical, analytical-synthetic, and comparative methodologies within a dialectical materialist framework, the research traces the development of Ho Chi Minh’s administrative thought and its practical application in building a modern political system. The paper discusses key principles such as democratic participation, public service ethics, administrative streamlining, and accountability, linking them to current administrative reform efforts in Vietnam. It argues that Ho Chi Minh’s vision remains crucial for creating a public administration that is people-centered, transparent, and responsive in the era of modernization and globalization. The findings provide insights for advancing administrative efficiency while preserving socialist democratic values.